2008
DOI: 10.2215/cjn.03280807
|View full text |Cite
|
Sign up to set email alerts
|

Value of a Complete or Partial Remission in Severe Lupus Nephritis

Abstract: Background and objectives: The value of a complete remission in severe lupus nephritis is well known but little is known about the impact of a partial remission in this patient population. The purpose of this study was to evaluate the long-term prognosis of achieving a complete or partial remission in a well-defined group of patients with severe lupus nephritis.Design, setting, participants, & measurements: In this study, 86 patients with diffuse lupus glomerulonephritis were reviewed for assessment of the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
176
3
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(209 citation statements)
references
References 33 publications
22
176
3
8
Order By: Relevance
“…IT overall efficacy (CR plus PR) turned to be 84.8%, with the rate of CR 35.3%, which is similar to Chen et al data [15] and higher than the ALMS study [17], probably because our study group included not only patients with LN lass III–V but also milder cases. Under ST, the rate of flares turned to be 19.2% during median follow-up of 12 [1; 236] months, similar to the data from the long-term follow-up of the MAINTAIN Nephritis Trial [18].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…IT overall efficacy (CR plus PR) turned to be 84.8%, with the rate of CR 35.3%, which is similar to Chen et al data [15] and higher than the ALMS study [17], probably because our study group included not only patients with LN lass III–V but also milder cases. Under ST, the rate of flares turned to be 19.2% during median follow-up of 12 [1; 236] months, similar to the data from the long-term follow-up of the MAINTAIN Nephritis Trial [18].…”
Section: Discussionsupporting
confidence: 88%
“…In patients who achieved PR, patient and kidney survival were 65% and 58%, respectively, and in nonresponders they were 35% and 0%, respectively. These differences confirm the positive prognostic value of complete and even partial LN response [15, 16], associated with significantly better outcomes compared to NR, and stress that failure to achieve renal response to immunosuppression negatively influences not only kidney but also patient survival.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In these patients, the risk reduction for the primary outcome was much greater than those in the NR group. The importance of PR has been suggested for various glomerulopathies (1,21,22). In particular, Reich et al indicated that patients with IgAN who initially presented with proteinuria .3 g/d and achieved PR (,1 g/d) had similar outcomes to patients with persistent proteinuria of ,1 g/d during follow-up and also had superior prognoses to patients who never achieved remission (1).…”
Section: Discussionmentioning
confidence: 99%
“…This may be important because the longer term outcome of treatment of lupus nephritis, measured as patient or renal survival, is significantly affected by the extent of the initial remission. 12 Partial as well as complete remissions have a salutary effect on long-term outcome of lupus nephritis. 12 The most consequential aspect of the trial by Bao et al is the short-term nature of the observations.…”
mentioning
confidence: 99%